Experimental investigation of the impact of gas generated via coal oxidation in the upstream coal goaf on the subsequent residual coal oxidation process - Baoyong Zhang; Jing Xing (Scientific Reports)
Abstract For large-scale goaf with a continuous air leakage flow field, it is imperative to elucidate the influences of the upstream airflow after coal oxidation on the downstream O2 consumption, heat release. In this paper, the temperature rise, O2 consumption, gas production, and heat release characteristics of coal along the direction of the airflow are analyzed in an experimental study on coal oxidation conducted in a 900 mm long coal sample tank utilizing program-controlled heating. The results suggest that as the temperature of the coal increases to 70–120 °C, there is a minimal difference in the O2 consumption rate between the inflow and middle sections, and this rate is significantly lower compared to that in the outflow section. After the temperature of the coal surpasses 120 °C, the O2 consumption and heat release in the inflow section reach their peak values. In contrast, at the same temperature, both the O2 consumption and heat release in the middle section exceed those in the outflow section. Moreover, if the O2 concentration of the inflow into the outflow section drops below 14.1%, and the temperature of coal in the outflow section exceeded 120 °C, this leads to a significant decrease in the CO production rate. The O2 consumption and heat release rates in the three sections are influenced by different factors. In the inflow section, the temperature and CO generation play significant roles. The middle section is affected by the incoming O2 concentration, CO production, and temperature. The outflow section is influenced by the incoming O2, CO, and CO2 concentrations and the CO2 generation.